2020
DOI: 10.1242/bio.055103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing methods to quantitatively validate TGFβ-dependent autophagy

Abstract: Transforming growth factor beta (TGFβ) promotes tumorigenesis by suppressing immune surveillance and inducing epithelial to mesenchymal transition (EMT). TGFβ may augment tumorigenesis by activating autophagy, which protects cancer cells from chemotherapy and promotes invasive and anti-apoptotic properties. Here, we assess how TGFβ1 modulates autophagy related (ATG) gene expression and ATG protein levels. We also assessed microtubule-associated protein light chain 3 (LC3) lipidation, LC3 puncta formation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…We previously reported that TGFβ1 induced ULK1 protein levels and stimulated autophagy in NSCLC cells ( Trelford and Di Guglielmo, 2020 ), however the mechanism of how this was achieved remained unknown. To this end, we first investigated if TGFβ1 alters AMPK and mTOR activity by following site-specific ULK1 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that TGFβ1 induced ULK1 protein levels and stimulated autophagy in NSCLC cells ( Trelford and Di Guglielmo, 2020 ), however the mechanism of how this was achieved remained unknown. To this end, we first investigated if TGFβ1 alters AMPK and mTOR activity by following site-specific ULK1 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…A549 cells stably expressing GFP-LC3 were treated with si-RNA against Smad4 or si-RNA targeting TRAF6 and TAK1 in combination with a p38 MAPK inhibitor for 24 h. Each experiment was conducted in the presence and absence of TGFβ1 for 24 h. LysoTracker Deep Red labeled lysosomes and Hoechst stain labeled the nucleus 2 h and 10 min prior to imaging, respectively. Imaging and quantitation was performed as previously described ( Trelford and Di Guglielmo, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations